Domestic Abuse and Child Health - Samantha Rawlings; Zahra Siddique (Institute for the Study of Labor (IZA), 2014)
We examine the effects of different kinds of domestic abuse (physical violence, emotional abuse, sexual abuse and physical violence while the victim is pregnant) on health outcomes of children born to victims. We use data on approximately 0.6 million children born between 1975 and 2013 across thirty different developing countries to investigate this relationship. Comparing children of abused mothers with otherwise similar children whose mothers were not victims of abuse, we find these children are 0.4 percentage points more likely to die within thirty days, 0.9 percentage points more likely to die within a year and 1.5 percentage points more likely to die within the first five years of being born. They are also 1.8 percentage points more likely to be low birth weight and, conditional on survival, 1.1 percentage points more likely to be stunted. Our findings allow us to quantify the costs of domestic abuse beyond costs borne directly by victims (or mothers) and gain a better understanding of the child health production process in a developing country context.
Keywords: I14; I15; J12; J13; 330; child health; domestic violence